Transición generacional en pequeñas y medianas empresas familiares (SMFB): Evidencia desde Italia - Mucelli, Attilio (2025)
The study is based on a multidisciplinary theoretical review, including agency theory, stewardship theory, and the socioemotional wealth perspective (Chrisman et al., 2007; Davis et al., 1997; Gómez-Mejía et al., 2007), to understand the challenges, critical factors, and strategies related to business succession. Methodologically, a case study is conducted in the Marche region, known for its high concentration of family microenterprises. The case analyzed illustrates how the lack of strategic planning and resistance to professionalization led to a business crisis, which was only reversed through the intervention of external actors and the sale to an industrial group. Among the main findings, the study highlights that small and medium family businesses (SMFBs) that adopt formal governance structures, successor training, and openness to external human capital exhibit higher rates of continuity and competitiveness. The article concludes with public policy recommendations to support generational succession, including tax incentives, legal support, and training programs in collaboration with universities and business associations. When well-managed, generational transition can become an opportunity for strategic renewal and the long-term sustainability of family businesses.